Regional Hereditary Cancer Program in Chile: A scalable model of genetic counseling and molecular diagnosis to improve clinical outcomes for patients with hereditary cancer across Latin America - Natalia Landeros; Laura Vargas-Roig; Silvina Denita; Alejandra Mampel; Rafael Hasbún; Hernán Araya; Iván Castillo; Camila Valdes; Marcela Flores; Juan Salgado Salter; Katherin Vasquez; Jacqueline Romero; et al. (Biological Research)
Abstract Background Breast cancer is a leading cause of cancer-related mortality worldwide, with hereditary forms accounting for approximately 10% of cases. In Chile, significant gaps exist in genetic counseling and testing, particularly within the public health system. This study presents the implementation and outcomes of the first regional hereditary cancer program in the Maule region of Chile, aimed at improving detection and management of hereditary breast cancer. Methods A cohort of 48 high-risk breast cancer patients from the Hospital Regional de Talca received genetic counseling and underwent Next-Generation Sequencing multigene panel testing. The program was established through collaboration between multiple institutions, leveraging telemedicine and outsourcing sequencing analysis to address regional gaps. Results Pathogenic or likely pathogenic variants were identified in 12% of patients, including in BRCA1, BRCA2, TP53, and PALB2. Notably, novel pathogenic variants in BRCA1 (rs80357505) and TP53 (rs1131691022) were discovered, highlighting the unique genetic landscape of the Chilean population. Additionally, 70 variants of uncertain significance were found across 42 genes, particularly in FAN1, MSH6, and FANCI, underscoring the need for further research. The program’s collaborative approach effectively bridged critical gaps in genetic services, providing high-quality care within the public health system despite limited resources. Conclusions The Regional Hereditary Cancer Program addresses significant gaps in genetic counseling and testing in Chile’s public health system. This scalable model enhances early detection and personalized treatment for hereditary cancer patients and could be adapted to other regions across Latin America.